The ambition and fortitude of African traders : a study of early local traders in the Transkeian territories, 1880-1910 - Tsokodibane, Kereeditse Optima (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.